Analysis of concentric bridge ring circular and square element for reflect array antenna: article / Nurhayati Md Saleh - Md Saleh, Nurhayati (2015)
This paper presents a study of phase slope, phase range and return loss for concentric bridge ring circular and square element for reflect array antenna by using single layer of substrate. The study has been done to find the best dimensions that suit the reflect array antenna criteria for both elements. Comparison of simulated results shows that concentric bridge ring circular element performs a better performance compare with concentric bridge ring square element that can be covered two frequency operation. All the process and development is done using CST MWS.